Exercise‐Dependent Modulation of Immunological Response Pathways in Endurance Athletes With and Without Atrial Fibrillation - Dorian, David; Gustafson, Dakota; Quinn, Ryan; Bentley, Robert F.; Dorian, Paul; Goodman, Jack M.; Fish, Jason E.; Connelly, Kim A. (Journal of the American Heart Association, 2024)
Atrial fibrillation (AF) is a common arrhythmia characterized by uncoordinated atrial electrical activity. Lone AF occurs in the absence of traditional risk factors and is frequently observed in male endurance athletes, who face a 2- to 5-fold higher risk of AF compared with healthy, moderately active males. Our understanding of how endurance exercise contributes to the pathophysiology of lone AF remains limited. This study aimed to characterize the circulating protein fluctuations during high-intensity exercise as well as explore potential biomarkers of exercise-associated AF. A prospective cohort of 12 male endurance cyclists between the ages of 40 and 65 years, 6 of whom had a history of exercise-associated AF, were recruited to participate using a convenience sampling method. The circulating proteome was subsequently analyzed using multiplex immunoassays and aptamer-based proteomics before, during, and after an acute high-intensity endurance exercise bout to assess temporality and identify potential markers of AF. The endurance exercise bout resulted in significant alterations to proteins involved in immune modulation (eg, growth/differentiation factor 15), skeletal muscle metabolism (eg, α-actinin-2), cell death (eg, histones), and inflammation (eg, interleukin-6). Subjects with AF differed from those without, displaying modulation of proteins previously known to have associations with incident AF (eg, C-reactive protein, insulin-like growth factor-1, and angiopoietin-2), and also with proteins having no previous association (eg, tapasin-related protein and α -Heremans-Schmid glycoprotein). These findings provide insights into the proteomic response to acute intense exercise, provide mechanistic insights into the pathophysiology behind AF in athletes, and identify targets for future study and validation.